Ensayos potenciodinámicos y espectroscopía de impedancia electroquímica en acero inoxidable para implantes quirúrgicos - Kociubczyk, Alex Iván (2014)
In the present work the corrosion resistance of stainless steels was evaluated following the specifications of ASTM F 745 standards. The specimens were obtained by two methods, the conventional process of investment castingand countergravity low pressure casting. Cyclic polarization tests were performed according to ASTM F 2129, using a conventional three-electrode cell. Pt electrode as a counter electrode and a saturated calomel (SCE) as a reference electrode was used. The experiments were performed at 37 ± 1 º C and before starting the test solution was purged with N2 gas for 15 minutes. As electrolyte a solution of NaCl 0.9% was used (pH7), the open circuit potential (OCP) was monitored for 1 hour and then the potentiodynamic scanning started in the anodic direction, at a speed of 0,167 mV . s-1 , since a potential of 100 mV below the OCP. The sweep was reversed after the threshold current density at a value of two greater than the current density of chopped decades. Measurements of electrochemical impedance spectroscopy (EIS) were after one hour of exposure of the specimens to PCAs performed in a frequency range of 100 kHz to 1 mHz and potential amplitude of ± 10 mV potential. The microstructure of the samples was analyzed before and after testing using optical microscopy (OM). The results indicate that the samples in general exhibit crack corrosion, and in some cases the occurrence of pitting corrosion was observed. Also, the capacity values were within the range corresponding to the electric double layer and the resistance to charge transfer increased on the specimens obtained by conventional casting in ceramic mold.